Automated irrigation system based on soil moisture using arduino board - Safwan A. Hamoodi; Ali N.Hamoodi; Ghanim M.Haydar (Institute of Advanced Engineering and Science, 2020)
In recent years, the best system of irrigation is studied by reducing the wasted amount of water and electricity. Automatic irrigation is the use of a device to operate irrigation structures so the change of flow of water from one bay, or set of bays, to another can occur in the absence of the irrigator. In this work, automatic control system of solar irrigation implemented practically using Arduino board. This photovoltaic (PV) system is applied in the garden of Engineering Technical College- Mosul (city in Iraq). PV system can be adjusted by many regions in Iraq where it planned to connect on small part of land. Irrigation process is controlled depending on moisture sensor that connected to sense the soil moisture and giving data to Arduino read pin. According to the program that uploaded to Arduino, DC pump can be controlled as ON-state or OFF-state as respect to the soil moisture percentage ratio. Finally, the practical results are approximately similar to that obtained from proteus Arduino simulator.